"Your count is zero" - counselling the infertile man - Wischmann, Tewes (Human fertility, 2013)
Little is known about the counselling needs of infertile men. Recent research has shown that suffering from involuntary childlessness may be nearly equally distributed between women and men, but men have more difficulty in communicating this emotional crisis, usually preferring an instrumental grieving style to regain a sense of control, whereas their female partners are often characterised by an intuitive grieving style such as the expression of feelings. When the specific counselling needs of infertile men are addressed adequately in an appropriate setting in the course of infertility counselling, high uptake rates can be achieved. In this paper, typical issues regarding infertility counselling for men are described and proposals to improve the psychosocial status of infertile men are given.
Gesehen am 18.11.2021